Democratic Leadership and Team Performance: Moderating Effect of Gender - Luitel, Riyana; Devkota, Niranjan; Dahal, Deepak (International Research Journal of MMC, 2024)
Team performance is a crucial part of a management working system in today’s world. The unity of the team determines the future that organization heads to. This study aims to identify the effects of democratic leadership on the team performance, and the moderating role of gender in these effects. Through the study of various research articles and published papers, it develops a simple regression model and assesses the dummy indicator regression of the variables used and discusses the results of analysis which indicates that democratic leadership has a positive and significant effect on team performance with p-value less than 0.05, the value of coefficient of multiple determination was 0.264. Likewise, the gender is moderating the impact of democratic leadership on team performance. This study attempts to provide some of the empirical support that there is a positive association between democratic leadership and team performance. This paper concludes with various implications which can be used by organizations to create leadership development courses that teach managers and supervisors how to lead democratically and gives research directions for future research study.